Carcinogenic human papillomavirus infection - Schiffman, Mark; Doorbar, John; Wentzensen, Nicolas; de Sanjosé, Silvia; Fakhry, Carole; Monk, Bradley J.; Stanley, Margaret A.; Franceschi, Silvia (Nature reviews. Disease primers, 2016)
Infections with human papillomavirus (HPV) are common and transmitted by direct contact. Although the great majority of infections resolve within 2 years, 13 phylogenetically related, sexually transmitted HPV genotypes, notably HPV16, cause — if not controlled immunologically or by screening — virtually all cervical cancers worldwide, a large fraction of other anogenital cancers and an increasing proportion of oropharyngeal cancers. The carcinogenicity of these HPV types results primarily from the activity of the oncoproteins E6 and E7, which impair growth regulatory pathways. Persistent high-risk HPVs can transition from a productive (virion-producing) to an abortive or transforming infection, after which cancer can result after typically slow accumulation of host genetic mutations. However, which precancerous lesions progress and which do not is unclear; the majority of screening-detected precancers are treated, leading to overtreatment. The discovery of HPV as a carcinogen led to the development of effective preventive vaccines and sensitive HPV DNA and RNA tests. Together, vaccination programmes (the ultimate long-term preventive strategy) and screening using HPV tests could dramatically alter the landscape of HPV-related cancers. HPV testing will probably replace cytology-based cervical screening owing to greater reassurance when the test is negative. However, the effective implementation of HPV vaccination and screening globally remains a challenge. Virtually all cervical cancers, a large fraction of other anogenital cancers and an increasing proportion of oropharyngeal cancers are caused by human papillomavirus (HPV) infection. Here, the authors describe HPV-driven carcinogenesis and discuss how developments in vaccines and screening tests could dramatically alter the landscape of HPV-related cancers worldwide.